Allylic and benzylic sp3 C–H oxidation in water. Issue 4 (20th November 2014) - Ang, Wei Jie; Lam, Yulin
Abstract : A copper-catalyzed method for the oxidation of allylic and benzylic sp 3 C–H by aqueous tert -butyl hydroperoxide (T-Hydro) in water using a recyclable fluorous ligand has been developed. Abstract : A copper-catalyzed method for the oxidation of allylic and benzylic sp 3 C–H by aqueous tert -butyl hydroperoxide (T-Hydro) in water using a recyclable fluorous ligand has been developed. The reaction procedure is tolerant to additional functional groups and the fluorous ligand could be reused with little loss of catalytic activity.